Effectiveness of Teachers ’ Motivational Strategies in Government Secondary Schools in Tanzania - Nzilano, Josta Lameck; Mwambapa, Lotina Mwambapa (Papers in Education and Development, 2022)
This study assessed the effectiveness of teacher motivational approaches in Government secondary schools in Tanzania. Six secondary schools found in Kyela district were used as a case study. The sample of the study includes a total of 194 respondents. Data collection methods used include questionnaires, semi-structured interviews, focus group discussion and direct field observations. The findings revealed a variety of teacher retention and motivation approaches that include setting of considerable teacher ' s workload, school working conditions and distance from home to school. Employer ' s recognition, reasonable pay, and training of teachers seemed to motivate them at work. The study recommends that schools and Government authorities should ensure reasonable pay, improved teacher training programmes and participation in decision-making. Keywords: collaborative decision, instructional supervision, motivation approaches, secondary schools, working conditions